The impact of digitizing healthcare services on hospital performance in the Kingdom of Saudi Arabia - Althaqafy, Samiyah Rafan; Barnawy, Mohammad Abdullah; Batawi, Faris Omar (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to analyze the impact of digitizing health services on hospital performance in the Kingdom of Saudi Arabia, within the context of the national direction toward digital transformation and the goals of Vision 2030 to advance the healthcare sector. The study population included all employees in hospitals across the Kingdom. A stratified random sampling method was used to select the sample, and 250 questionnaires were distributed, with 232 returned representing a response rate of 92.8%.The study adopted a descriptive-analytical approach to examine the relationship between digitization (independent variable) and hospital performance (dependent variable), using a measurement tool comprising four key dimensions, administered to a scientifically determined sample.The findings revealed a statistically significant relationship between the dimensions of healthcare digitization and hospital performance, with an overall mean score of 3.87 and an agreement rate of 77.32%. The results also indicated significant differences in the level of adoption, with digital infrastructure and health information systems being more widely implemented than management information systems.The study also identified several barriers to the adoption of digital healthcare services in Saudi hospitals, primarily related to funding, administrative capacity, availability of suitable technologies, and qualified human resources. It recommended enhancing digitalization efforts in Saudi hospitals and learning from the experiences of leading countries in this domain.
Keywords: Digitization; healthcare services; hospital performance; healthcare digitization; Saudi Arabia